Frame analysis in analyzing Ukrainian female media images - Andriievska, Valeriia (Global Prosperity, 2023)
This research takes a gender-based problem Ukrainian magazines as research object, analyzing the characteristics of its reports on Ukrainian social gender issues and Ukrainian female media images, and analyzing the audiences’ views to feminism and Ukrainian women, analyzing the role of media in promoting the development of feminism and the changes in Ukrainian women’s social status. To investigate the constructed text and the impact it has on sociocultural and ideological events, frame analysis was applied, being combined with other methods such as text analysis, discourse analysis, and semiotic analysis. It was determined that framing allows to choose certain aspects of reality and make them more visible in the communicative process, leading to a particular interpretation. The conclusion was made that feminist discourse is inherent in publications on various topics: politics, culture, and science, whereas the frame of "feminism" is associated with few publications; most publications are associated with the frame of "gender".